MEMBANGUN START UP BERBASIS USAHA MINUMAN BERBAHAN DASAR LOKAL - Darmanto, Erlambang Budi (Dharma: Jurnal Pengabdian Masyarakat, 2024)
The culinary business itself from year to year has not changed much and continues to exist in people's lives. In addition, the culinary business has a high level of resilience, so it has a huge opportunity and promises Foodstart to utilize media and technology to introduce and offer these selling products. Foodstart up focuses on developing a food business based on local wisdom and existing natural resources. This is done in various ways such as through establishing a business or startup related to food production, food or beverage processing. One of the businesses that have been very profitable and promising in recent years is the contemporary beverage business, one of which is chocolate and tea drinks, namely flytea and flychoco. However, there are several problems, namely: (1) There are many flytea and flychoco enthusiasts, but the stand or boot is still limited. (2) Flytea and flychoco marketing which is still carried out door to door.